1999
DOI: 10.1073/pnas.96.16.9051
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence that the rifamycin polyketide synthase assembles polyketide chains processively

Abstract: The assembly of the polyketide backbone of rifamycin B on the type I rifamycin polyketide synthase (PKS), encoded by the rifA-rifE genes, is terminated by the product of the rifF gene, an amide synthase that releases the completed undecaketide as its macrocyclic lactam. Inactivation of rifF gives a rifamycin B nonproducing mutant that still accumulates a series of linear polyketides ranging from the tetra-to a decaketide, also detected in the wild type, demonstrating that the PKS operates in a processive manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
130
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 30 publications
5
130
0
1
Order By: Relevance
“…However, mutant strain MT0031ABH, in which a 21 kb fragment of the post-PKS modification genes has been deleted, did not accumulate proansamycin X, but instead the tetraketides SY4b and desacetyl-SY4b were produced. These compounds have previously been isolated from knock-out mutants of the amide synthase RifF, as a result of premature release of the polyketide chain intermediates from the enzyme, starting from the tetraketide through the undecaketide (Stratmann et al, 1999;Yu et al, 1999). Structure identification of these intermediates showed that from the pentaketide onwards they contain a naphthalene ring, suggesting that the formation of the naphthalene moiety of rifamycin B takes place during the chain extension of the polyketide, specifically between the tetraketide and the pentaketide stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, mutant strain MT0031ABH, in which a 21 kb fragment of the post-PKS modification genes has been deleted, did not accumulate proansamycin X, but instead the tetraketides SY4b and desacetyl-SY4b were produced. These compounds have previously been isolated from knock-out mutants of the amide synthase RifF, as a result of premature release of the polyketide chain intermediates from the enzyme, starting from the tetraketide through the undecaketide (Stratmann et al, 1999;Yu et al, 1999). Structure identification of these intermediates showed that from the pentaketide onwards they contain a naphthalene ring, suggesting that the formation of the naphthalene moiety of rifamycin B takes place during the chain extension of the polyketide, specifically between the tetraketide and the pentaketide stage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on results of the present study and others (Stratmann et al, 1999;Yu et al, 1999), it was clear that the core naphthalene ring moiety of rifamycin is constructed during the polyketide chain extension process. However, the fact that the reaction may require a catalytic enzyme, whose gene is located in the post-PKS modification region and functions in trans with the PKS, is rather unusual.…”
Section: Inactivation Of Rif-orf3mentioning
confidence: 99%
See 2 more Smart Citations
“…However, recombinant RifF lacked any measurable INH acetylation activity (13). RifF catalyzes the release of the completed polyketide from the rifamycin type I polyketide synthase by intramolecular amide formation, yielding proansamycin X (26). Intramolecular amide formation appears to proceed by a reaction mechanism similar to that of the N acetylation by NAT.…”
mentioning
confidence: 99%